2023
DOI: 10.3390/rs15143590
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Alteration Minerals Using ZY-1 02D Hyperspectral Remote Sensing Data in Coalbed Methane Enrichment Areas

Abstract: As a clean energy resource, coalbed methane (CBM) is an important industry in China’s dual-carbon strategic planning. Despite the immense potential of CBM resources in China, the current exploration level remains low due to outdated survey technology, impeding large-scale exploration and development. This study investigates the application of hyperspectral data in CBM enrichment areas, specifically focusing on the extraction of alteration minerals in the Hudi coal mine area of the Qinshui Basin using ZY-1 02D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Given the utilization of L2D PRISMA data, significant processing steps have been undertaken on this dataset. However, owing to the specific nature of these data and the necessity to assess the Earth's surface reflection, certain bands within this dataset prove unsuitable for mineral remote sensing studies [30,31]. These bands exhibit heightened sensitivity to water vapor, resulting in substantial absorptions within the spectral profile.…”
Section: Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the utilization of L2D PRISMA data, significant processing steps have been undertaken on this dataset. However, owing to the specific nature of these data and the necessity to assess the Earth's surface reflection, certain bands within this dataset prove unsuitable for mineral remote sensing studies [30,31]. These bands exhibit heightened sensitivity to water vapor, resulting in substantial absorptions within the spectral profile.…”
Section: Pre-processingmentioning
confidence: 99%
“…These bands exhibit heightened sensitivity to water vapor, resulting in substantial absorptions within the spectral profile. Notably, the absorption characteristics spanning (913 nm to 979 nm), (1078 nm to 1185 nm), (1317 nm to 1491 nm), and (1775 nm to 2044 nm) diminish the efficacy of absorption ranges crucial for mineralogical investigations [31]. Hence, the primary course of action entails the exclusion of these bands from further analysis.…”
Section: Pre-processingmentioning
confidence: 99%
“…As shown in Table 4, the MSK-RFFIM method resulted in enhanced accuracy compared with either the MSK or RFFIM method alone. Previous studies have also indicated that hybrid feature selection methods can enhance the overall effectiveness of feature selection (Chen et al, 2023;Wang et al, 2023). The MSK-RFFIM method was further analyzed using the top 20 bands from Input V3, Input V4, and Input V5 (refer to Table 5).…”
Section: Feature Selectionmentioning
confidence: 99%
“…In addition, compared to traditional remote sensing data, hyperspectral data can provide richer spectral information, thus reflecting the spectral response characteristics of different lithologies more accurately. This can provide effective technical support for geological exploration and mineral resource development (Chen L. et al, 2023).…”
Section: Introductionmentioning
confidence: 99%